2022
DOI: 10.34067/kid.0008302021
|View full text |Cite
|
Sign up to set email alerts
|

Do Proton-Pump Inhibitors Cause CKD and Progression of CKD?: COMMENTARY

Abstract: This is an Early Access article. Please select the PDF button, above, to view it. Be sure to also read the PRO: 10.34067/KID.0007622021 and the CON: 10.34067/KID.0005852021

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Following adjustment for potential confounders such as baseline conditions of comorbidities, concomitant medications, baseline kidney function (baseline eGFR), sex and age, PPI users demonstrated a significantly higher rate of transition from G3 to G4 or G5 stages compared to H2B users, suggesting that PPI usage is associated with increased risk of CKD progression. These findings align with previous research indicating an association between PPI use and an increased risk of CKD progression [ 8 , 14 , 18 ]. Furthermore, we construed transitions to lower eGFR stages (i.e., larger eGFR values) as improvements or fluctuations, notwithstanding prevailing beliefs regarding the irreversibility of kidney function decline [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Following adjustment for potential confounders such as baseline conditions of comorbidities, concomitant medications, baseline kidney function (baseline eGFR), sex and age, PPI users demonstrated a significantly higher rate of transition from G3 to G4 or G5 stages compared to H2B users, suggesting that PPI usage is associated with increased risk of CKD progression. These findings align with previous research indicating an association between PPI use and an increased risk of CKD progression [ 8 , 14 , 18 ]. Furthermore, we construed transitions to lower eGFR stages (i.e., larger eGFR values) as improvements or fluctuations, notwithstanding prevailing beliefs regarding the irreversibility of kidney function decline [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…The underlying mechanism of PPI usage with adverse effects on CKD remains the subject of an ongoing inquiry. Plausible explanations include the induction of acute interstitial nephritis (AIN) [ 17 , 18 ] and hypomagnesemia [ 19 ] by the usage of PPIs. Delayed treatment or incomplete recovery from AIN can lead to acute kidney disease, potentially increasing the risk of developing CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, though PPIs should be used with vigilance, there is currently no need for wide adoption of de-escalation strategies with regard to long-term PPI use merely out of safety concerns [ 29 ]. The use of PPI cannot be the sole reason for renal damage when used concomitantly with nephrotoxic drugs [ 30 ]. Similarly, Moayyedi et al also showed that chronic pantoprazole use had no significant between-group difference between pantoprazole and placebo for incident events of CKD (2.1% vs. 1.8%; p=0.15) [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
“…The risk factors for CKD include age, smoking, alcohol consumption, diabetes mellitus, and hypertension. Therefore, it is imperative that we focus on preventive and curative approaches of CKD ( 2 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Model 4: adjusted for age, gender, race/ethnicity, education level, income-to-poverty ratio, caffeine intake, energy intake, diabetes mellitus history, and hypertension history. The specific range for the tertile: dietary OBS: T1 [2-13]; T2[13][14][15][16][17][18][19][20]; T3[20][21][22][23][24][25][26][27][28][29][30][31]; Lifestyle OBS: T1 [0-3]; T2[3][4]; T3[4][5][6][7][8].…”
mentioning
confidence: 99%